A Narrative Literature Review : Is Cosmetic Breast Implants Safe for Women? - Vina Luthfiana Hasna; Salman Salman; Indah Laily Hilmi (Jurnal EduHealth, 2023)
In order to maintain, obtain, and take care of beauty from day to day, cosmetics have always played an important role in women’s lives to overcome these problems. The use of cosmetics used by women is based on a beauty standard which of course varies in each country. The most common beauty standards are physical beauty, character beauty (inner beauty), white skin, and proportional body sizes. The existence of these beauty standards sometimes makes women feel dissatisfied with their physique, even for some people, changing their physique or changing body size by performing plastic surgery is a natural thing. One of the most common plastic surgery procedures worldwide is breast augmentation through implants. The frequency of surgical procedures requiring breast implants in recent years has continued to increase. In the 1980s, when the third generation of silicone implants were introduced, widespread public health concerns began to emerge about the adverse effects of breast implants. The purpose of this review article is to discuss the safety of breast implants in women based on the relevant scientific evidence. Although not all symptoms and effects of breast implants can appear in all users of breast implants, this review can help women to make the right decision regarding breast implant procedures.